Pengendalian Parameter Produktivitas pada Rekonstruksi Jalan Rigid berdasarkan Jadwal LOB (Line Of Balance) (Studi Kasus : Proyek Rekonstruksi Jalan Penganten – Ngampal) - Saputra, Ichwan Hadi; Al Ma’ruf, Fadhil Zaid; Santoso, Toni Budi (Innovative: Journal Of Social Science Research, 2025)
In the world of construction, there is repetitive work. For projects with similar elements, scheduling is needed that can meet resource needs in a sustainable and orderly manner without obstacles. The purpose of this research is to calculate the amount of Labor, Materials and Equipment required to achieve the specified schedule on the Penganten - Ngampal Road Reconstruction project using the Line Of Balance (LOB) method. The steps taken include conducting interviews and collecting project data in the form of RAB, Time Schedule, MC 0 / MC 100 which are then processed into a Line Of Balance (LOB) diagram. The results of the productivity analysis, labor requirements include 362 workers, 206 fitters and 113 foremen. Material requirements include Aggregate A, Liquid Asphalt/Emulsion Bonding Layer, Wear Layer Laston, Structural Concrete fc' 10 - 30 MPa, Formwork Plate, Polytene, Curing Compound, Joint Sealant, Expansion Cap (3/4“ Pipe), Reference Wood, Multiplex, Nails, 2” Pipe, Plain and Fin Reinforcing Steel, Concrete Wire, Painting, Selected Materials, Woven Steel Wire. Meanwhile, for equipment Excavator, Dump Truck, Bulldozer, Tandem, Water Tanker, Baby Vibrator Roller, Motor Grader, Chainsaw, Track Loader, Hand Auger Drill, Concreter Vibrator.